The Effect of Halal Labelling of Medicine on Customer’s Purchase Interest at Karunia Sehat Baru Pharmaceutical Semarang - Purnami, Islina Dewi; Sawitri, Agustina; Ummaya, Ulfa Ulli (Indonesian Journal of Medical and Pharmaceutical Science, 2022)
Background: Halal labeling is the inclusion of halal writing or statements on product packaging to indicate that the product in question has the status of a halal product. The purpose of this study was to determine the effect of halal labeling on drugs on customer buying interest at the Karunia Sehat pharmacy in Semarang. Methods: The population in this study were all customers who came to the gift health pharmacy, and the number of samples needed was 96 respondents. Data was collected by distributing questionnaires directly to customers using a linkert scale and then scoring. Results: Based on data analysis, halal labeling on medicinal products are "very influential" on customer buying interest with a percentage of 71.9% which is in the 41-50 score category. Conclusion: halal labeling on medicinal can affect on customer’s purchase interest at Karunia Sehat Baru Pharmaceutical Semarang.